Pengaruh Customer Experience terhadap Minat Berkunjung Kembali ke Atraksi Wisata Kebun Raya Cibinong - Yessy Auliya Yunesfi; Vitha Octavanny; Nungky Puspita (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The fluctuation in visitor numbers at Cibinong Botanical Garden indicates the need to understand factors influencing tourists’ intention to revisit. This study aims to examine the effect of customer experience dimensions on revisit intention at Cibinong Botanical Garden. A quantitative approach was employed using purposive sampling, involving 100 visitors aged over 18 years who had visited the destination at least once. Data were collected through structured questionnaires measured on a Likert scale and analyzed using multiple regression with IBM SPSS. The results show that customer experience simultaneously has a significant effect on revisit intention (F = 61.923; p < 0.001). However, partially, only the educational dimension has a significant positive influence (t = 2.314; p = 0.023), while comfort, hedonic, novelty, safety, and beauty dimensions are not statistically significant (p > 0.05). The adjusted R² value of 0.124 indicates that 12.4% of revisit intention is explained by the six dimensions, while the remainder is influenced by other factors. These findings highlight the importance of strengthening educational programs to enhance visitor loyalty.